PENGKAJIAN KAPASITAS DAYA DUKUNG TANAH GAMBUT DIDAERAH PENGEMBANGAN IRIGASI DI KALIMANTAN TENGAH - Affandi, Diah (Jurnal Air Indonesia, 2009)
Piles and pile foundations have been in use since prehistoric time. The commonest function of piles is to transfer a load that cannot be adequately supported at shallow depths to a depth where adequate support becomes available. When a pile passes through poor material and its tip penetrates a small distance into a stratum of good bearing capacity it is called a bearing pile. When piles are installed in a deep stratum of limited supporting ability and these piles developed their carrying capacity by friction on the sides of the pile, they are called friction piles. Many times the load carrying of piles results from a combination of point resistance and skin friction.Ã‚Â  The load taken by a single pile can be determined by static load test. The allowable load is obtained by applying a factor of safety to the failure load. Although it is expensive, a static load test is the only reliable means of determining allowable load on a friction pile. In this case,Ã¢â‚¬Å“CerucukÃ¢â‚¬Â are widely used in foundation engineering to increase bearing capacity of the foundation andreduce the settlement.Ã‚Â Keywords : Pile foundation, bearing capacity, skin friction.